Profile of families with undernourished children interned in an institution in the city of Fortaleza-Ceará - Kucharski, Fernanda Aguiar; Araújo, Cristiana Belchior de; Silva, Raimunda Magalhães da; Fernandes, Ana Fátima Carvalho (Rev Rene, 2002)
The desnutrition is a nutrition disease where is an inadequate dietetic ingestion that results on low nutritional reserves that correspond on lose of weight, growing retard and immunity reduction. The study object identify the desnutritioned children’s families profile. This is an descriptive and exploratory research happened on an institution of desnutrition prevent in Fortaleza, Ceará, with 10 mother who were interned with their children between may and june of 2001. The information’s were obtained by interviews and on the results we found the main aspects were: low economic and social factor, 70% of the mother didn’t have the first degree (of the school) complete, 60% of the mothers have problems on accessing the health services, the most part of the children are under 3 months, and where the motherly milk is very important 50% of the children never had the motherly milk. We conclude that these factors contributed for desnutrition braking up and a big part of the mothers didn’t know the necessity and benefit that they could obtain by an adequated health assistance.